Educational radio and digital social media: perspectives and challenges of the Radio Unesp FM fanpage - Vicente, Maximiliano Martin; Versuti, Christiane Delmondes (Organicom, 2015)
The article discusses the use of the fanpage by Radio Unesp FM, a public radio station (of the São Paulo State University) withcultural and educational characteristics. To achieve this readings were obtained from educational radio stations, radio andInternet and organizations in the social media, and an analysis was conducted of the broadcasts from January to June 2014,using data generated by Facebook Insights. It is expected that this work will show ways to improve the use of this platformnot only for Radio Unesp, but also by other educational stations, so as to obtain success in their goals of disseminatingcontent related to education, culture and citizenship.